2-(2-Methoxyphenoxy)-3-nitropyridine - Nasir, S.B.; Fairuz, Z.A.; Abdullah, Z.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
In the title compound, C(12)H(10)N(2)O(4), the pyridine and benzene rings are almost orthogonal, forming a dihedral angle of 86.63 (6)degrees. Each of the nitro [O-N-C-C torsion angle = -6.45 (19)degrees] and methoxy [C-O-C-C torsion angle = 179.69 (11)degrees] groups is almost coplanar with the ring to which it is connected. Molecules are consolidated in the crystal structure via C-H center dot center dot center dot O interactions, forming a three-dimensional network.